Modeling of Petri Net (software development) / Abd. Malik Ab. Rahim - Ab. Rahim, Abd. Malik (1999)
This thesis presents a Petri net approach to modeling. simulation and control of the manufacturing system. Petri net is a formal model of information flow. The major use of Petri net is to model system of events. It briefly reviews applications of the Petri net to batch process plant (e.g. bottling plant and simple machine shop). The thesis introduces definitions and concepts of Petri nets. It discusses the basic of Petri net modules in system modeling, the modeling method and an example of practical system. System modeling is an important stage in design and implementation of discrete event systems. This allows detection design problems originated from incomplete or ambiguous specification. On other hand, for existent systems, the analysis of the model can detect the behavioral problems and provide measures of performance. In general, Petri net is a graphical, mathematical and process of modeling tooi for engineers in automatic control and computer science, that applicable to many other systems. It plays a major role in improving the batch control scheme. Petri net-based simulation consists an interactive execution of the net.